For x, a>0 the roots of the equation ${{\log }_{ax}}a+{{\log }_{x}}{{a}^{2}}+{{\log }_{{{a}^{2}}x}}{{a}^{3}}=0$ is (are) given by
(a) ${{a}^{-\dfrac{4}{3}}}$
(b) ${{a}^{-\dfrac{3}{4}}}$
(c) ${{a}^{-\dfrac{1}{2}}}$
(d) ${{a}^{-\dfrac{2}{3}}}$
Answer
Verified
509.7k+ views
Hint: First convert out given expression using the formula, ${{\log }_{a}}x=\dfrac{\log a}{\log x} ,\log (cd)=\log c+\log d,\log \left( {{d}^{n}} \right)=n\log d$. Then divide the whole expression by common term. Then transform the obtained expression using ${{\log }_{a}}x=t$, then find the value of ‘t’ and then transform it to get values of x in terms of a.
Complete step-by-step answer:
We are given that for x, a > 0 we have to find the roots of equation
${{\log }_{ax}}a+{{\log }_{x}}{{a}^{2}}+{{\log }_{{{a}^{2}}x}}{{a}^{3}}=0.............\left( i \right)$
Now to proceed the equation we have to use formula such as,
${{\log }_{c}}d=\dfrac{\log d}{\log c}$
By using this we can transform equation (i) as,
$\dfrac{\log a}{\log ax}+\dfrac{\log {{a}^{2}}}{\log x}+\dfrac{\log {{a}^{3}}}{\log {{a}^{2}}x}=0............\left( ii \right)$
Now we will use the formula such as,
log(cd) = log c +log d
By using this we can write equation (ii) as,
$\dfrac{\log a}{\log a+\log x}+\dfrac{\log {{a}^{2}}}{\log x}+\dfrac{\log {{a}^{3}}}{\log {{a}^{2}}+\log x}=0............\left( iii \right)$
Now we will use the formula such as,
$\log \left( {{d}^{n}} \right)=n\log d$
By using this we can write the equation (iii) as,
$\dfrac{\log a}{\log a+\log x}+\dfrac{2\log a}{\log x}+\dfrac{3\log a}{2\log a+\log x}=0............\left( iv \right)$
Now we will divide log a from both numerator and denominator of the term of equation (iv) we get,
$\dfrac{1}{1+\dfrac{\log x}{\log a}}+\dfrac{2}{\dfrac{\log x}{\log a}}+\dfrac{3}{2+\dfrac{\log x}{\log a}}=0...............\left( v \right)$
In equation (v) we will use the formula, $\dfrac{\log c}{\log d}={{\log }_{d}}c$ we get,
$\dfrac{1}{1+{{\log }_{a}}x}+\dfrac{2}{{{\log }_{a}}x}+\dfrac{3}{2+{{\log }_{a}}x}=0..............\left( vi \right)$
Now we will substitute ${{\log }_{a}}x=t$ , we will transform equation (vi) as
\[\dfrac{1}{1+t}+\dfrac{2}{t}+\dfrac{3}{2+t}=0............\left( vii \right)\]
Taking LCM in (vii) we get,
$\dfrac{t\left( 2+t \right)+2\left( 1+t \right)(2+t)+3t\left( t+1 \right)}{\left( 1+t \right)t\left( 2+t \right)}=0$
On cross multiplication we get,
t(2 + t) + 2(1 + t)(2+t) +3t (t + 1) = 0
On further simplification we get,
$\begin{align}
& 2t+{{t}^{2}}+2(2+t+2t+{{t}^{2}})+3{{t}^{2}}+3t=0 \\
& \Rightarrow 2t+{{t}^{2}}+4+2t+4t+2{{t}^{2}}+3{{t}^{2}}+3t=0 \\
\end{align}$
On simplification we get,
$6{{t}^{2}}+11t+4=0$
This is a quadratic equation. We will solve it by splitting the middle term, we get
$\begin{align}
& 6{{t}^{2}}+8t+3t+4=0 \\
& \Rightarrow 2t\left( 3t+4 \right)+1\left( 3t+4 \right)=0 \\
& \Rightarrow (3t+4)(2t+1)=0 \\
& \Rightarrow 3t+4=0,2t+1=0 \\
& \Rightarrow t=-\dfrac{4}{3},t=-\dfrac{1}{2} \\
\end{align}$
So, finally the value for $t=\dfrac{-4}{3},\dfrac{-1}{2}$.
We had assumed,
${{\log }_{a}}x=t$
Substituting the value of ‘t’, we get
${{\log }_{a}}x=\dfrac{-4}{3}$ and ${{\log }_{a}}x=-\dfrac{1}{2}$
Now we will use the transformation that is, ${{\log }_{b}}a=c\Rightarrow a={{b}^{c}}$. By using this in above equation, we get
$x={{a}^{-\dfrac{4}{3}}}$ and $x={{a}^{\dfrac{-1}{2}}}$ respectively.
Therefore, the correct answer is option (a) and (c).
Note: Students should be careful while calculating and finding values of ${{\log }_{a}}x$ also using transformation of changing ${{\log }_{a}}x=t$as $x={{a}^{t}}$.
Another way to solve the quadratic equation is using the formula, $t=\dfrac{-b\pm \sqrt{{{b}^{2}}-4ac}}{2a}$.
Complete step-by-step answer:
We are given that for x, a > 0 we have to find the roots of equation
${{\log }_{ax}}a+{{\log }_{x}}{{a}^{2}}+{{\log }_{{{a}^{2}}x}}{{a}^{3}}=0.............\left( i \right)$
Now to proceed the equation we have to use formula such as,
${{\log }_{c}}d=\dfrac{\log d}{\log c}$
By using this we can transform equation (i) as,
$\dfrac{\log a}{\log ax}+\dfrac{\log {{a}^{2}}}{\log x}+\dfrac{\log {{a}^{3}}}{\log {{a}^{2}}x}=0............\left( ii \right)$
Now we will use the formula such as,
log(cd) = log c +log d
By using this we can write equation (ii) as,
$\dfrac{\log a}{\log a+\log x}+\dfrac{\log {{a}^{2}}}{\log x}+\dfrac{\log {{a}^{3}}}{\log {{a}^{2}}+\log x}=0............\left( iii \right)$
Now we will use the formula such as,
$\log \left( {{d}^{n}} \right)=n\log d$
By using this we can write the equation (iii) as,
$\dfrac{\log a}{\log a+\log x}+\dfrac{2\log a}{\log x}+\dfrac{3\log a}{2\log a+\log x}=0............\left( iv \right)$
Now we will divide log a from both numerator and denominator of the term of equation (iv) we get,
$\dfrac{1}{1+\dfrac{\log x}{\log a}}+\dfrac{2}{\dfrac{\log x}{\log a}}+\dfrac{3}{2+\dfrac{\log x}{\log a}}=0...............\left( v \right)$
In equation (v) we will use the formula, $\dfrac{\log c}{\log d}={{\log }_{d}}c$ we get,
$\dfrac{1}{1+{{\log }_{a}}x}+\dfrac{2}{{{\log }_{a}}x}+\dfrac{3}{2+{{\log }_{a}}x}=0..............\left( vi \right)$
Now we will substitute ${{\log }_{a}}x=t$ , we will transform equation (vi) as
\[\dfrac{1}{1+t}+\dfrac{2}{t}+\dfrac{3}{2+t}=0............\left( vii \right)\]
Taking LCM in (vii) we get,
$\dfrac{t\left( 2+t \right)+2\left( 1+t \right)(2+t)+3t\left( t+1 \right)}{\left( 1+t \right)t\left( 2+t \right)}=0$
On cross multiplication we get,
t(2 + t) + 2(1 + t)(2+t) +3t (t + 1) = 0
On further simplification we get,
$\begin{align}
& 2t+{{t}^{2}}+2(2+t+2t+{{t}^{2}})+3{{t}^{2}}+3t=0 \\
& \Rightarrow 2t+{{t}^{2}}+4+2t+4t+2{{t}^{2}}+3{{t}^{2}}+3t=0 \\
\end{align}$
On simplification we get,
$6{{t}^{2}}+11t+4=0$
This is a quadratic equation. We will solve it by splitting the middle term, we get
$\begin{align}
& 6{{t}^{2}}+8t+3t+4=0 \\
& \Rightarrow 2t\left( 3t+4 \right)+1\left( 3t+4 \right)=0 \\
& \Rightarrow (3t+4)(2t+1)=0 \\
& \Rightarrow 3t+4=0,2t+1=0 \\
& \Rightarrow t=-\dfrac{4}{3},t=-\dfrac{1}{2} \\
\end{align}$
So, finally the value for $t=\dfrac{-4}{3},\dfrac{-1}{2}$.
We had assumed,
${{\log }_{a}}x=t$
Substituting the value of ‘t’, we get
${{\log }_{a}}x=\dfrac{-4}{3}$ and ${{\log }_{a}}x=-\dfrac{1}{2}$
Now we will use the transformation that is, ${{\log }_{b}}a=c\Rightarrow a={{b}^{c}}$. By using this in above equation, we get
$x={{a}^{-\dfrac{4}{3}}}$ and $x={{a}^{\dfrac{-1}{2}}}$ respectively.
Therefore, the correct answer is option (a) and (c).
Note: Students should be careful while calculating and finding values of ${{\log }_{a}}x$ also using transformation of changing ${{\log }_{a}}x=t$as $x={{a}^{t}}$.
Another way to solve the quadratic equation is using the formula, $t=\dfrac{-b\pm \sqrt{{{b}^{2}}-4ac}}{2a}$.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
The correct order of melting point of 14th group elements class 11 chemistry CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE